2021
DOI: 10.1038/s41598-020-80503-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailable fluoride in calcium-containing dentifrices

Abstract: Calcium added to dentifrices can complex with fluoride ions to reduce intra-oral bioavailability and therefore efficacy in preventing dental caries. Six commercially available dentifrices containing different types of calcium and fluoride were analyzed for total and bioavailable fluoride levels by adding 10 g of dentifrice to 30 mL of distilled deionized water and mixing vigorously for 1 min to simulate toothbrushing. One milliliter of the dentifrice/water slurry was immediately centrifuged and the supernatant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Similarly, the study of Shen et al (2021) found that the presence of saliva and biofilm is crucial to authenticate the mechanism of action of CPP-ACP in remineralization [ 29 , 30 ]. The amount of secreted saliva and saliva pH can both alter the way CPP-ACP remineralizes tooth enamel as CPP separates from ACP in the acidic environment [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the study of Shen et al (2021) found that the presence of saliva and biofilm is crucial to authenticate the mechanism of action of CPP-ACP in remineralization [ 29 , 30 ]. The amount of secreted saliva and saliva pH can both alter the way CPP-ACP remineralizes tooth enamel as CPP separates from ACP in the acidic environment [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the study of Shen et al (2021) found that the presence of saliva and bio lm is crucial to authenticate the mechanism of action of CPP-ACP in remineralization [27]. The amount of secreted saliva and saliva pH can both alter the way CPP-ACP remineralizes tooth enamel as CPP separates from ACP in the acidic environment [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the formation of uorapatite is a self-limiting phenomenon, which prevents the penetration of calcium and phosphate into deeper layers [29]. Evidence shows that CPP-ACP (bioactive component of GC Tooth Mousse) causes greater remineralization than uoride, which has been attributed to the availability of calcium and phosphate ions [30,31]. CPP stabilizes the calcium phosphate on the enamel surface such that in a FluoroDose ® , GC Tooth Mousse and 52S4/UPGO, n 5, SD standard deviation).…”
Section: Discussionmentioning
confidence: 99%